Fungal contamination and mycotoxins associated with sorghum crop: its relevance today - Astoreca, Andrea Luciana (2019)
Sorghum grain is the fifth most produced cereal in the world. The dietary ingestion of sorghum along with other cereals is a way to take advantage of the grain’s numerous benefits for human health. However, sorghum is now threatened by several fungal diseases that reduced crop yields and quality with substantial economic losses. Numerous fungal genera have been associated with the contamination of sorghum grains collected from different countries around the world, including the main mycotoxigenic genera. The main fungi that infect sorghum grains belong to Aspergillus and Fusarium genera, associated with the production of aflatoxins, fumonisins, zeralenone and deoxynivalenol, being the aflatoxins the main risk in this crop. Sorghum, unlike other cereals, does not yet have legislation that regulates the maximum content of mycotoxins in grains for its commercialization. As mycotoxins in food and feed are one of the main food safety problems worldwide, this work provides an in-depth examination into the occurrence of mycoflora and mycotoxins in sorghum. The current data compilation highlights the imperative need for sorghum-producing countries to strengthen surveillance and increase grain inspections to ensure the safety of this crop for human consumption as well as the need to establish regulations for mycotoxins or groups of mycotoxins in sorghum.